Upaya Menuju Demokratisasi Pendidikan - Teguh Sihono (Universitas Negeri Yogyakarta, 2011)
The new paradigm education providing in order to capable produce results the generation who was came to play the role of nation young society be a live process and stating affair. Education expected will became efficacious medicine for medicine society disease. This importance are there base aspect the thing which necessary renewed that is regulation, professionalism, and management.Purpose education create the thing which democratic or education democratization, the state was make UU No. 22- 1999 year, UU No. 32-2004 year (Regional autonomy), UU No. 20- 2003 year (Sisdiknas), PP No 19-2005 year (SPN), Permendiknas No. 22, 23, 24 -2006 year (KTSP implementation). Implementation curriculum of KTSP the thing which give the right and freedom, community participation, organizer authority, supporter institution, and stakeholder’s, there is as like real effort for creates education democratization in Indonesia. In order that capable the human resources which qualified, and superiority competitiveness.